Narrative Literature Review on MC4R rs17782313 Gene-Nutrient Interaction and Obesity Risk - Yocku, Monica H.S. Otline; Pramono, Adriyan (Jurnal Kesehatan, 2025)
The Melanocortin 4 Receptor (MC4R) gene plays a critical role in appetite regulation and energy balance. The single nucleotide polymorphism (SNP) rs17782313, located near the MC4R gene, has been widely associated with an increased risk of obesity, primarily through its influence on appetite control and energy homeostasis. Understanding how this genetic variant interacts with dietary intake can offer valuable insights into the pathophysiology of obesity and inform personalized nutritional strategies. This study aims to investigate the role of SNP rs17782313 in dietary factors and obesity risk, with a particular focus on the underlying molecular mechanisms. A narrative literature review was conducted, synthesizing findings from molecular, genetic, and epidemiological studies. The review highlights how rs17782313 may influence MC4R function and how macronutrient intake, particularly carbohydrates, proteins, and fats, modulates this effect. Evidence suggests that nutritional factors can affect gene expression or interact directly with the MC4R pathway, influencing energy intake, metabolic responses, and body weight regulation. Observational studies in various populations confirm the global relevance of these gene-diet interactions. The findings highlight the need for an integrative approach that combines genetics and nutrition to develop individualized interventions for obesity prevention and treatment. Understanding these interactions may contribute to more effective management of obesity and related metabolic disorders by tailoring dietary recommendations to genetic profiles.